A study on the prevalence and related factors of frailty and pre-frailty in the older population with diabetes in China: A national cross-sectional study - Zeng, Xuezhai; Jia, Na; Meng, Lingbing; Shi, Jing; Li, Yingying; Hu, Xing; Hu, Jiabin; Xu, Hongxuan; Li, Jianyi; Li, Hui; Qi, Xin; Wang, Hua; et al. (Frontiers in Public Health, 2022)
OBJECTIVE To investigate the prevalence of frailty and pre-frailty and its associated factors in older Chinese patients with diabetes through a nationwide cross-sectional study. RESEARCH DESIGN AND METHODS The data were obtained from the Sample Survey of the Aged Population in Urban and Rural China (SSAPUR), conducted in 2015, which was a cross-sectional study involving a nationally representative sample of older adults aged 60 years or more from 31 provinces, autonomous regions, and municipalities in mainland China. Subjects with diabetes were included in this study. Frailty index, based on 33 potential deficits, was used to categorize individuals as robust, pre-frail, or frail. RESULTS A total of 18010 older patients with diabetes were included in this study. The weighted prevalence of frailty and pre-frailty in older patients with diabetes in China was 21.8% (95%CI 21.2%-22.4%) and 58.5% (95%CI 57.8%-59.3%), respectively. The prevalence of frailty and pre-frailty among older patients with diabetes from different provinces/municipalities/autonomous regions was significantly different. Multinomial logistic regression analysis showed living alone, poor economic status, ADL disability, and comorbidities were strongly correlated with frailty and pre-frailty in older patients with diabetes. CONCLUSIONS Frailty and pre-frailty are common in older patients with diabetes in China, and exhibit sociodemographic and geographic differences. In the clinical setting of older adults with diabetes, there is a need to increase awareness of frailty and to advance the early diagnosis and intervention of frailty.